Mexican Mathematical Talent Program (TAMME) – Enrichment Activities for Elementary and High School Students - Zarzar, Cristianne Butto; Fernández, Joaquín Delgado; Capellini, Vera Lúcia Messias Fialho [UNESP] (FapUNIFESP (SciELO), 2023)
The study aimed to identify students with mathematical talent in Elementary and High School, with regard to the Mayan and Babylonian numerical system for Elementary School and computational thinking, with the use of Scratch for High School; to design and implement an out-of-school enrichment program with Elementary and High School students; to study the evolution of mathematical ideas, worked on in the extracurricular enrichment program. Theoretical support was based on the School Wide Enrichment Model (SEM). This model is originated from Renzulli’s Triadic Enrichment Model. The results presented refer to extracurricular enrichment activities, with Babylonian numerals and the Mayan numerical system, and activities in the Scratch environment. The results of the study showed that both age groups were able to approach the proposed activities and developed learning experiences that gave them skills to solve mathematical problems, both in the pencil and paper environment and in the Scratch programming language. The group of Elementary School students represented numbers in the Mayan and Babylonian system and performed arithmetic operations; in this way, this work helped them to understand the positional system; and the High School students learned to make animations of two characters (sprites) and learned how to program.
Programa Talento Matemático Mexicano (TAMME) - Atividades de Enriquecimento para Alunos de Ensino Fundamental e Médio
Keywords: Extracurricular enrichment program; Mathematical talent; Primary education; Renzulli model; Secondary Education